Optimal timing for percutaneous coronary intervention in patients undergoing transcatheter aortic valve implantation. (15th October 2022) - Lunardi, Mattia; Venturi, Gabriele; Del Sole, Paolo Alberto; Ruzzarin, Alessandro; Mainardi, Andrea; Pighi, Michele; Pesarini, Gabriele; Scarsini, Roberto; Tavella, Domenico; Gottin, Leonardo; Ribichini, Flavio Luciano
Abstract: Background: The best timing to perform percutaneous coronary interventions (PCI) in patients undergoing TAVI is unknown. Most PCI are performed before TAVI, because of concerns about potential ischemic complications during valve implantation. In this study we aimed to compare short-and long-term outcomes of patients undergoing PCI before or after TAVI. Methods: Patients undergoing TAVI and PCI from 2010 to 2021 were analyzed. PCI was defined as high-risk when involving unprotected left main, proximal left anterior descending, proximal dominant right coronary artery or 3-vessel disease. The primary endpoint was the cumulative incidence of any TAVI procedural complication and in-hospital adverse events (VARC-3 criteria). Results: Out of 1162 patients, 144 underwent PCI, 68% after TAVI, 78.4% of which were at high-risk. The primary endpoint occurred in 28.4% of patients in PCI pre-TAVI group vs 21.4% in PCI post-TAVI group ( p = 0.403) and in 34.4% vs 17.3% of patients respectively among high-risk patients ( p = 0.075). A higher rate of stroke was observed in the PCI pre-TAVI group regardless of the PCI complexity (6.5% vs 0.0%, p = 0.031; 9.3% vs 0.0% p = 0.025 in the high-risk group). At 24 months, MACCE-free survival was lower in patients who underwent PCI before TAVI (84.4% vs 97.9%, adjusted HR 10.16, 95% CI 1.19–86.57, p = 0.019; and 84.4% vs 97.3%, adjusted HR 7.34 95% CI 0.78–62.28 p = 0.082 in the high-risk group). Conclusions: PCI performed after TAVI does not expose patients to higher risks of peri-procedural hazards and provides a trend towards favourable clinical outcome at mid-to-long term. Graphical abstract: Unlabelled Image Highlights: The best timing for PCI in TAVI patients has not been defined yet. PCI after TAVI showed similar if not better outcomes (i.e. lower strokes). PCI after TAVI may include safe use of debulking technique (i.e. rotational atherectomy). PCI after TAVI may allow a more accurate and reliable CAD functional assessment.